Tantangan Dakwah Digital: Perspektif Herbert Marcuse - Danur Putut Permadi (UIN Raden Mas Said Surakarta, 2023)
Digitalization that occurs in human life is inevitable. This has implications for the da'wah process that everyone can feel through various media. Social media has now succeeded in shifting the classic paradigm of da'wah. This paper aims to examine the extent of the transformation of da'wah that occurred during Pandemi Covid-19. Based on a qualitative approach, this study found that da'wah digestion occurred as an implication of social change during the pandemic. Indonesian people who experience a cultural concurrent then try to maximize social media in an effort to meet their needs for spritation. The switching of da'wah activities to the digital world provides a confirmation that post -pandemic society is a digital community. The current condition of the community when viewed from the point of view of Herbert Marcuse is a one -dimensional community. Digitalization of da'wah carried out during Pandemi hints that the community prioritizes pseudo needs, where social media is considered completely important. In addition, with the digitalization of da'wah, people can be trapped in what Marcuse calls the imperium image. Conditions where the appearance dominates the conversation compared to what is the discussion.